The princess of convenient plot devices. 2 /Kazusa Yoneda ; original story, Mamecyoro ; character design, Mitsuya Fuji ; translation, Sarah Moon ; lettering, Phil Christie. - Mamecyoro; Yoneda, Kazusa (Yen Press, 2023)
"Determined to change her fate...Princess Octavia heads to the junior ball to find herself a (fake) boyfriend! But before she even arrives, she runs into trouble...when her entourage crosses paths with an out-of-control carriage. As it turns out, the passenger was traveling to the same party in secret before the driver mysteriously fainted. Entangled in a series of rumors and conspiracies, the only one Octavia can count on is her bodyguard, Klifford...In all the chaos, does she have any chance of scoringa faux beau?"--